Phylogeny of Neotropical Seirinae (Collembola, Entomobryidae) based on mitochondrial genomes. (15th January 2020) - Godeiro, Nerivânia Nunes; Pacheco, George; Liu, Shanlin; Gioia Cipola, Nikolas; Berbel‐Filho, Waldir Miron; Zhang, Feng; Gilbert, Marcus Thomas P.; Bellini, Bruno Cavalcante
Abstract: Seirinae is one of the most diverse subfamilies of Collembola. To date no detailed phylogeny of Seirinae has been proposed, which leads to difficulties in the understanding of evolutionary patterns regarding this taxon. The main aim of this study is to clarify the phylogenetic relationships within the Neotropical Seirinae, by generating and analysing the mitochondrial genomes of 26 terminal taxa of Entomobryidae, and one species of Paronellidae. Specifically, we first generated Illumina HiSeq 2000 shotgun sequence data from each species, then reconstructed the mitochondrial genome of each species using two methods: MitoZ and MIRA/MITOBim. Using these data, we were able to generate a well‐supported phylogeny that combined all the above species as well as three publicly available mitogenomes from other species. Bayesian and maximum likelihood methods were applied using all 13 protein coding genes. In this way, monophyly for the internal groups of Seirinae was obtained based on molecular evidence for the first time, as was the potential validity of three main internal taxa of the subfamily. We furthermore validated that Tyrannoseira is a distinct lineage and propose the elevation of Lepidocyrtinus to genus. Lastly, we anticipate that these newly available mitogenomes will serve as a useful dataset for future studies on the evolution of the Collembola and Hexapoda.